2014
DOI: 10.1037/neu0000024
|View full text |Cite
|
Sign up to set email alerts
|

Reading in subjects with an oral cleft: Speech, hearing and neuropsychological skills.

Abstract: Objective Evaluate speech, hearing, and neuropsychological correlates to reading among children, adolescents and young adults with non-syndromic cleft of the lip and/or palate (NSCL/P). Method All testing was completed in one visit at a Midwestern university hospital. Subjects in both the NSCL/P (n = 80) and control group (n = 62) ranged in age from 7 to 26 years (average age = 17.60 and 17.66, respectively). Subjects completed a battery of standardized tests evaluating intelligence, neuropsychological skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 40 publications
3
70
0
3
Order By: Relevance
“…Working memory, which is commonly assessed using number span tasks similar to those employed in the current study, has been previously associated with written arithmetical calculation (Andersson, 2008). Similarly, working memory has been shown to be a strong and unique correlate of word reading performance in children, adolescents, and young adults with iCL/P (Conrad et al, 2014). In the current study, working memory was a significant correlate of arithmetical calculation for the control group, but was just below the threshold of statistical significance for the group with iCL/P ( β = .173. p = .053).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Working memory, which is commonly assessed using number span tasks similar to those employed in the current study, has been previously associated with written arithmetical calculation (Andersson, 2008). Similarly, working memory has been shown to be a strong and unique correlate of word reading performance in children, adolescents, and young adults with iCL/P (Conrad et al, 2014). In the current study, working memory was a significant correlate of arithmetical calculation for the control group, but was just below the threshold of statistical significance for the group with iCL/P ( β = .173. p = .053).…”
Section: Discussionmentioning
confidence: 96%
“…However, there have been a number of studies that have evaluated the underlying neuropsychological variables involved in the basic reading outcomes of this population, with findings consistently implicating auditory working memory and rapid naming as major predictors (Conrad et al, 2015). Given the common cognitive demands of reading and mathematics, it was hypothesized that working memory and rapid naming would be significant neuropsychological correlates of arithmetical calculation for the iCL/P group, just as they had been shown to be significant correlates of reading in previous iCL/P studies (Conrad et al, 2014; Richman & Ryan, 2003). Interestingly, the neuropsychological correlates of arithmetical calculation for the control and iCL/P groups included in this study were fairly similar.…”
Section: Discussionmentioning
confidence: 99%
“…Deficits in neuropsychological skills associated with reading and spelling (i.e., phonological awareness, memory, and rapid labeling) have been documented among children with iCL/P (Chapman, 2011; Collett, Stott-Miller, Kapp-Simon, Cunningham, & Speltz, 2010; Conrad, DeVolder, McCoy, Richman, & Nopoulos, 2014; Lee, Young, Liow, & Purcell, 2015; Richman & Ryan, 2003). Large-scale population studies have found deficits in reading achievement compared to matched controls (Wehby, Collett, Barron, Romitti, & Ansley, 2015; Wehby et al, 2014).…”
Section: Reading Developmentmentioning
confidence: 99%
“…29 A recent study from our lab has found that for children with ICLP, performance on an auditory memory task was most strongly predictive of single-word reading abilities (while measures of speech quality and hearing had no association with reading outcomes). 32 Interestingly, although being predictive, auditory memory was not significantly lower in children with ICLP, possibly indicating an overreliance on auditory memory to compensate for other missing skills important to reading.…”
Section: Reading Skills In Iclpmentioning
confidence: 90%
“…5,6 However, several other studies have found NO association between early speech and hearing problems and later reading outcomes, leading to a question as to the etiology of these reading difficulties. [32][33][34] This question of etiology is critical in terms of finding appropriate treatments for reading disabilities in this population. The current dyslexia-based intervention model focuses on treatment of phonological awareness difficulties, when these may not be the root of the disability in children with cleft.…”
Section: Reading Skills In Iclpmentioning
confidence: 99%